Adolf Melezinek and engineering pedagogy - V. M. Prikhod’Ko; Z. S. Sazonova (Высшее образование в России)
The origin and development of engineering pedagogy in Russia and in the foreign countries are analyzed. The principal role of professor Adolf Melezinek in the creation of the International society for the engineering pedagogy (IGIP) is discussed. Не is the founder of this society, and it is due to his efforts the prerequisites for the professional-pedagogical training of technical disciplines teachers’ were created. Thus engineering pedagogy has gained the scientific fundamentals, and that makes it an important factor for the training of competitive engineers.